Theory and migration. Towards a framework of migration and human actions - Olof Stjernström (Cybergeo, 2004)
The following article discusses the role of the human agency in migration theory. In connection to that special interest is focused on the structuration-theory where the human agent plays an important role. The relationship between the structuration-theory on the one hand and the concept of time-geography on the other hand is discussed. It is argued for that the development in time-geography towards micro-simulation approaches opens new doors for the debate concerning the relation environment – human agency. At the end the article argues for a combined approach where migration is understood from two viewpoints; the structuration theory and the time-geography.